Public expenditures, aid and economic growth – some empirical evidence from the Portuguese autonomous regions - António Almeida (European Regional Science Association (ERSA), 2004)
The financial perspectives in the after 2006 are clearly unfavourable for the Portuguese autonomous regions. Financial resources and investment will be channelled to the Easter Europe, and only the outer-most regions able to convince about their specificity (and need for substantial financial support) will receive similar levels of financial transfers. Like the majority of small island economies, the Madeira economy depends on a restricted group of sectors. It's unquestionable that the EU transfers are decisive in the dynamics of the regional economy. Therefore, post-2007 perspective is not encouraging, which is a concerning scenario. The communitarian funds transfers and tourism have a great effect on the economy dynamics. We intended to contribute to the on-going debate providing some empirical evidence about the importance of the EU and national transfers in the Portuguese autonomous regions.
Keywords: 330